The Optimization of a Numerical Steel Foundry Simulation Through a Characterization of the Thermal Properties of the Materials - Souêtre, Morgan; Vaucheret, Alexis; Jacquet, Philippe; Carton, Jean-François (Journal of Casting & Materials Engineering, 2022)
In many foundries, numerical simulation is used to determine the origins of different defects as this tool allows the acceleration of the design process. However, the databases provided by different software do not seem to tally with the actual properties of the material. In fact, every foundry uses a different grade of steel and varying mixtures of sand. An evaluation of the impact of different material properties showed the importance of measuring every physical property to improve the database of the software. Following this, an experiment was conducted to evaluate the gap between numerical simulations and the results obtained through experimentation. This experiment, called thermal analysis, consists in measuring the solidification and cooling of a cylinder filled with liquid steel. After the calculation of the steel properties and a simulation with real experimental parameters, a comparison between each cooling curve was realized. This comparison shows that the calculated properties provide a simulated cooling curve which is closer to the experimental curve than the properties in the original database. We did not explore all of the metal properties in this study, but the modification of the sand properties was explored, together with the thermal conductivity of the steel and sand. These other measurements will be obtained in a future study.